Genetic and Epigenetic Heterogeneity and the Impact on Cancer Relapse - Hassan, Ciaran (Exp Hematol, 2017)
Acute myeloid leukemia (AML) is an aggressive hematopoietic malignancy with an exceedingly poor prognosis, showing a 5-year overall survival rate of 40–45% in the young and a 5-year survival rate of below 10% in the elderly (>60y). Though a high percentage of patients enter complete remission following chemotherapeutic intervention, the majority of patients relapse within three years. Such stark prognostic outcomes highlight the need for additional clinical research, basic discovery, and molecular delineation of the etiologies and mechanisms behind responses to therapy that lead to relapse. Here we summarize recent discoveries in tumor heterogeneity at the genetic and epigenetic levels, and their independent molecular trajectories and dynamics in response to therapy. These new discoveries may have significant implications for understanding, monitoring, and treating leukemia and other cancers.